Ultra-long-term follow-up of renal denervation in patients with resistant hypertension and mild chronic kidney disease - Wang, L; Zhang, H; Li, C; Yin, X M; Li, Z Q; He, Q; Sun, X Q; Xia, D C; Kong, D L; Lu, C Z (Zhōnghuá xīnxuèguănbìng zázhi, 2025)
To investigate the ultra-long-term antihypertensive efficacy, safety, major adverse events, and survival benefits of renal denervation (RDN) in patients with resistant hypertension (rHTN) and mild chronic kidney disease (CKD). This real-world, single-center retrospective study enrolled patients with rHTN and mild CKD who underwent RDN at Tianjin First Central Hospital between October 2011 and June 2016. Office blood pressure, home self-measured blood pressure, 24-hour ambulatory blood pressure, serum creatinine, estimated glomerular filtration rate, and urine albumin-to-creatinine ratio were collected at baseline and at 1, 5, and 13 years post-RDN. The total daily defined dose of antihypertensive medications at 13 years post-RDN was recorded, along with endpoint events during follow-up, including cardiovascular death, all-cause death, hospitalization for heart failure, myocardial infarction, and stroke. Patients were stratified according to CKD stage (G1-G2 vs. G3a) and baseline systolic blood pressure (mild-